Antibiotic Classification and Indication Review for the Infusion Nurse. Issue 1 (January 2017) - Percival, Kelly M.
Abstract : Outpatient parenteral antimicrobial therapy (OPAT) has become an increasingly common practice for the treatment of infections. The infusion nurse plays a vital role in administering, monitoring, and educating patients about parenteral antibiotics, while bridging communication between the patient and OPAT team. It is important for the infusion nurse to know common indications, adverse effects, monitoring parameters, and the mechanism of action for antibiotics used in OPAT to provide optimal patient care. This review includes those antibiotics, which are frequently administered or recently approved with a high likelihood of being used in OPAT.